Significance of voxel-based morphometry in studying mild cognitive impairments - A. I. Damulina; R. N. Konovalov; A. S. Kadykov (Анналы клинической и экспериментальной неврологии, 2017)
Cognitive impairments are an important medical and socialproblem associated with a high prevalence of this disease in thepopulation. 46% of patients develop dementia within 5 years afterthe diagnosis of mild cognitive impairments (MCIs). Voxelbasedmorphometry (VBM) is a modern neuroimaging techniquewell-proven in studying dementia. VBM in a combinationwith neuropsychological examination of patients enables clarifyingthe genesis of mild cognitive impairments (MCIs) and predictingfurther development of the disease as early as the initialstage of the pathology.